1965
DOI: 10.1139/v65-354
|View full text |Cite
|
Sign up to set email alerts
|

A L.E.T. INDEPENDENT DOSIMETER BASED ON THE CHEMILUMINESCENT DETERMINATION OF H2O2

Abstract: A sensitive method for the determination of Hz02 based on the copper-catalyzed chemilu~ninescent reaction between luminol and H202 has been developed. The integral luminescence measured with a modified spec:trophotofluorometer was found to increase linearly with concentration for 3 X low8 t o 1.5 X ill H202 solutions. This method was applied to the determination of Hz02 formed in irradiated water and it was shown t h a t this system may be used as a dosimeter in the range 30 t o 3 000 rads. The following value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1968
1968
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…This luminol test gave a qualitative indication of the presence of hydrogen peroxide and could no doubt be made more quantitative by adopting the procedures of Armstrong and Humphreys (1965). However as Table III shows measurements of the oxygen consumption in the presence of catalase could also provide this quantitative information.…”
Section: Solution Bovine Serummentioning
confidence: 98%
“…This luminol test gave a qualitative indication of the presence of hydrogen peroxide and could no doubt be made more quantitative by adopting the procedures of Armstrong and Humphreys (1965). However as Table III shows measurements of the oxygen consumption in the presence of catalase could also provide this quantitative information.…”
Section: Solution Bovine Serummentioning
confidence: 98%
“…During study of luminol CL using Cu(II) as the catalyst we observed that some CL emission results even when no hydrogen peroxide is present. Previous studies of the effect of Cu(II) on the luminol reaction do not mention such an occurrence (13)(14)(15)(16)(17). Because this effect had not been reported previously and because it is normally held that Fe(II) is the only common metal ion capable of catalyzing the CL luminol reaction in the absence of hydrogen peroxide (2), we have investigated further.…”
mentioning
confidence: 96%
“…The lower limit (detection limit) was defined as the concentration of peroxide which gives a CL signal equivalent to 3tfb, where ab is the standard deviation of the blank signal. The detection limits presented here in the presence of the CTAC reversed micelles are 1 or 2 orders of magnitude poorer than those obtained with catalyzed (or enzymatic) luminol oxidation systems in water if based on an initial peroxide sample concentration basis (34,65,(68)(69)(70). The detection limits calculated in terms of the initial aqueous peroxide concentration are 4.4 X 6 M and 7.1 X 10"6 M for the peak height and the integrated CL signal, respectively.…”
Section: -26)mentioning
confidence: 61%
“…This is not surprising since the slope has been reported to depend upon such factors as pH, luminol concentration, and type of catalyst used (33). For example, the slope varied from 1.3 to 0.94 in the Cu(II) catalyzed system, from 1.4 to 1.1 in the microperoxidase or hematin system, and from 2 to 1 in the horseradish peroxidase system (34,69). This reflects the intrinsic complexity of the mechanism and stoichiometry of the luminol-hydrogen peroxide oxidation reaction system (33).…”
Section: -26)mentioning
confidence: 99%
See 1 more Smart Citation